Coordinating Leadership Supports for Teachers' Instructional Improvement. Issue 3 (May 2019) - Gibbons, Lynsey Kay; Wilhelm, Anne Garrison; Cobb, Paul
Principals and instructional coaches are asked to organize their schools to support teachers' ongoing professional learning. Prior studies have examined what principals do to support coaches rather than the ways they work together to support instructional improvement. We build on prior studies by examining how principals and coaches coordinate their work to support instructional improvement. To examine coordination, we selected cases in which coaches were or were not successful in interacting with teachers around teaching mathematics. We then analyzed the data within and across each of four cases. In schools where coaches were identified as successful in interacting with teachers, principals and coaches coordinated their work across three settings in order to jointly support teachers: teacher collaborative meetings, classroom visits, and coach–principal informal meetings. This study contributes to the literature on leadership by specifying how principals and coaches can coordinate their individual and collective work to organize supports for teachers.